Effect of Mg and TiB on the Mechanical Properties of A356 Aluminium Alloy Base Materials With Die Casting Process - EI Bhiftime (BIOMEJ, 2022)
The development of research on aluminum base materials is very rapid at this time. Aluminum base material reinforced with Mg and TiB particles by the die casting method is the simplest way. The purpose of this study was to see the effect of wt.% Mg and the addition of TiB on the mechanical properties of Al356MgTiB alloy. AlSi was used as a matrix reinforced by Mg with a percentage variation of (3, 4, 5 wt%) and TiB 2 wt%. The method used is die casting. In the casting process, the material is melted down to a liquid state at a temperature of 800 oC. After that the temperature was lowered to a stirring temperature of 640 oC. Then heated again to a pouring temperature of 760 oC. The density value obtained increased with the addition of Mg variation, namely the variation of Mg 4%wt 2.69 g/cm3. The porosity value obtained decreased, namely the variation of the 5%wt Mg element, namely 5.19%. The hardness value of Al356MgTiB alloy increases with the addition of Mg. The highest hardness is achieved at the percentage of Mg 5%wt, which is 65.41 HRB or an increase of 33% from the hardness of the base material. The value of tensile strength increases with the addition of Mg. The highest tensile strength is found in the 4%wt Mg variation, which is 198.4 MPa. The %EL value decreased with the addition of Mg and TiB. The decrease in %EL is accompanied by an increase in the strength of the material. The research was conducted by testing density, hardness testing, and tensile testing.